CD24 and Siglec-10 Selectively Repress Tissue Damage-Induced Immune Responses - Chen, Guo-Yun (2009)
Patten recognition receptors, which recognize pathogens or components of injured cells (danger), trigger activation of the innate immune system. Whether and how the host distinguishes between danger- versus pathogen-associated molecular patterns remains unresolved. We report that CD24-deficient mice exhibit increased susceptibility to danger- but not pathogen-associated molecular patterns. CD24 associates with high mobility group box 1 (HMGB1), heat shock protein 70 (HSP70) and heat shock protein 90 (HSP90), negatively regulates their stimulatory activity and inhibits nuclear factor-kappa B (NF-κB) activation. This occurs at least in part through CD24 association with Siglec-10 in humans or Siglec-G in mice. Our results reveal that the CD24-Siglec G pathway protects the host against a lethal response to pathological cell death and discriminates danger- versus pathogen-associated molecular patterns.